Predictive superiority of abdominal obesity measures over body mass index in Indian hypertensive adults - Gupta, Prakhar; Meena, Kamal; Gupta, Aankury; Gavli, Jai (Asian Journal of Medical Sciences, 2024)
Background: Obesity has emerged as an epidemic and is known to be associated with multiple co-morbidities, contributing to increased morbidity and mortality. Body-mass index (BMI) has been traditionally used to assess obesity in an individual but abdominal obesity markers are being claimed to have a stronger association with adverse cardiovascular outcome as compared to BMI. However, there are only a few studies that have evaluated these indices in Asian Indians. Aims and Objectives: The study was conducted to compare BMI and waist measurement based indices among hypertensive adults and their association with adverse cardiovascular outcomes. The secondary objectives were to determine any gender-based differences among anthropometric indices and improved predictability on adding waist-based indices to BMI. Materials and Methods: An observational study was conducted to analyse association of anthropometric indices such as BMI, A body shape index (ABSI), Waist–hip ratio (WHR), Waist-to-height ratio (WHtR), Lean body mass-to-weight ratio, and Waist circumference (WC), with risk of cerebrovascular accidents (CVA) and coronary artery disease (CAD) in Indian hypertensive adults. Results: In total, 400 participants were included and female subjects were noted to have higher prevalence of obesity in our study population. Only 33.25% patients had BMI in recommended range and the numbers were even lower for WHtR and WHR. BMI and ABSI were found to have a weak association with development of co-morbidities while measures of abdominal obesity such as WHR, WC, and WHtR were found to have consistently strong association with CVA and CAD with high sensitivity and negative predictive values. Conclusion: More accurate markers of abdominal obesity can help in better assessment of cardiovascular risk among high-risk population to improve the overall outcome. Easy to use, outpatient-based markers such as WC, WHR, and WHtR appear to be better than BMI in risk assessment.